Short-term rental of residential real estate in selected cities of the world – modeling and implementation of indicators for profitability assessment - Paweł Oktaba; Malgorzata Grzywińska-Rąpca; Karol Wojtowicz (Journal of Modern Science, 2024)
Objectives Assessment of the profitability of short-term rentals in selected cities around the world.